Response of Broilers to Feeding Manipulations - Oyedeji, J.O.; Atteh, J.O. (International Journal of Poultry Science, 2005)
The study investigated the response of broilers to different feeding manipulations. Six groups of day old Anak broilers were randomly assigned to either one of the following feeding methods from day old to 3 weeks; Ad libitum feeding, Skip-a-day feeding, 50% of ad libitum feeding, 6 hours of light and 18 hours of darkness per day, 3% dietary ammonium sulphate or diet containing 18% protein and 2800 kcal/kg ME. Broilers were thereafter fed the same finisher diet to market age. Results at market age showed that feed intake was significantly reduced by all but one of the feed restriction methods investigated (P< 0.05, P<0.01). Weight gains were comparable among broilers regardless of the feeding method (P>0.05, P>0.01). Feed to gain ratio was significantly reduced in broilers placed on 50% of ad libitum feeding (P<0.05, P<0.01). Feeding methods did not affect broilers liveability (P>0.05, P>0.01). Cost to benefit ratio of broiler production was significantly reduced by skip-a-day and 50% of ad libitum feeding methods (P<0.05, P<0.01). Also abdominal fat pad, a factor that downgrades carcass value was significantly reduced by skip-a-day and 6 hours of lighting per day feeding methods (P<0.05, P<0.01). It was concluded that for both cost and abdominal fat reduction, skip-a-day feeding method for 3 weeks would offer the best alternative to the usual ad libitum feeding in broilers.